2017
DOI: 10.1371/journal.pone.0174084
|View full text |Cite
|
Sign up to set email alerts
|

Disrespect and abuse of women during childbirth in Nigeria: A systematic review

Abstract: BackgroundPromoting respectful care at childbirth is important to improve quality of care and encourage women to utilize skilled delivery services. However, there has been a relative lack of public health research on this topic in Nigeria. A systematic review was conducted to synthesize current evidence on disrespect and abuse of women during childbirth in Nigeria in order to understand its nature and extent, contributing factors and consequences, and propose solutions.MethodsFive electronic databases were sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
175
6
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(207 citation statements)
references
References 33 publications
14
175
6
12
Order By: Relevance
“…Younger women with no education and younger women with some education were more likely to experience verbal abuse, compared with older women (≥30 years) [14]. In a cross-sectional study by Okafor et al in Enugu State in Nigeria, 20% of women reported discrimination on the basis of ethnicity, low social class, young age and HIV seropositive status, however, in four cross-sectional studies, women of low socioeconomic status and with no formal education reported experiences of unfriendly and harsh attitudes of staff in higher proportions [12]. Women in labor have a need for companionship, empathy and help, and descriptive studies of women's childbirth experiences have suggested four dimensions to the support that they want during labor: emotional support, informational support, physical support and advocacy [20].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Younger women with no education and younger women with some education were more likely to experience verbal abuse, compared with older women (≥30 years) [14]. In a cross-sectional study by Okafor et al in Enugu State in Nigeria, 20% of women reported discrimination on the basis of ethnicity, low social class, young age and HIV seropositive status, however, in four cross-sectional studies, women of low socioeconomic status and with no formal education reported experiences of unfriendly and harsh attitudes of staff in higher proportions [12]. Women in labor have a need for companionship, empathy and help, and descriptive studies of women's childbirth experiences have suggested four dimensions to the support that they want during labor: emotional support, informational support, physical support and advocacy [20].…”
Section: Discussionmentioning
confidence: 93%
“…Studies show that younger women, women with a low education level, rural residents and primiparas reported discrimination and unfriendly behaviors by providers and staff in the delivery room. As a result, they were not satisfied with their labor care [12][13][14]. No research could find on this subject in the Kurdistan region of Iraq; therefore, I investigated midwives' and physicians' communication skills in the delivery room in Erbil city, Iraq.…”
Section: Introductionmentioning
confidence: 99%
“…Respectful Maternity Care (RMC) has been recognized as an essential strategy for improving quality and utilization of maternity care [6]. It is defined as a universal human right that encompasses the principles of ethics and respect for women's feelings, dignity, choices and preferences [7]. Indeed, RMC is an approach to care which emphasizes the fundamental rights of women, newborns, and families, and that enhances adequate access to evidence-based care while recognizing the unique needs and preferences of both women and newborns [8].…”
Section: Plos Onementioning
confidence: 99%
“…It is around a decade that promoting Respectful Maternity Care (RMC) has been recognized as an essential strategy for improving quality and utilization of maternity care [6]. It is defined as a universal human right that encompasses the principles of ethics and respect for women's feelings, dignity, choices and preferences [7]. Indeed, RMC is an approach to care which emphasizes the fundamental rights of women, newborns, and families, and that enhances adequate access to evidence-based care while recognizing the unique needs and preferences of both women and newborns [8].…”
Section: Introductionmentioning
confidence: 99%